Pelatihan Merancang Koding Terintegrasi Materi IPA Bagi Guru SD Aisyiyah Mataram - Islahudin Islahudin; Haifaturrahmah Haifaturrahmah; Hamzah Hamzah; Riski Mini Rupiarti; Heni Heni; Ririn Arianti (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service activity involved partner institutions, namely SD Aisyiyah 1 Mataram and SD Aisyiyah 2 Mataram. The objectives of this community service program were: (1) to improve thinking, reading, and writing skills, as well as other required skills (soft skills and hard skills), through the design of coding activities integrated with science subject matter; and (2) to enhance the ability to apply coding within science learning to support school extracurricular activities. The method employed in this community service activity consisted of four stages: (1) the first stage, preparation prior to the implementation of the activity; (2) the second stage, mentoring and training; (3) the third stage, presentation and consultation of coding products resulting from the training; and (4) the fourth stage, implementation of the training outcomes in the classroom learning process. Based on these stages, it can be concluded that: (1) 95% of classroom teachers were able to recognize and understand coding applications based on Scratch; and (2) 95% of classroom teachers were able to design Scratch-based coding integrated with science content, particularly GLB and (GLBB, with learning outcomes improving from a moderate pre-test score (52.4%) to a high post-test score (74.2%).Abstrak: Kegiatan pengabdian ini memiliki mitra yaitu SD Aisyiyah 1 Mataram dan SD Aisyiyah 2 Mataram. Tujuan pengabdian ini yaitu 1) meningkatkan keterampilan berpikir, membaca dan menulis atau keterampilan lain yang dibutuhkan (softskill dan hardskill) melalui perancangan koding terintegrasi materi IPA; 2) meningkatkan kemampuan menerapkan koding ke dalam materi IPA untuk mendukung pembelajaran ektrakurikuler sekolah. Metode yang digunakan pada kegiatan pengabdian ini terdiri dari 4 tahap yaitu 1) tahap pertama: persiapan sebelum pelaksanaan kegiatan, 2) tahap kedua: pendampingan dan pelatihan, 3) tahap ketiga: presentasi dan konsultasi produk koding hasil pelatihan, tahap 4) tahap keempat: penerapan hasil pelatihan pada proses pembelajaran di kelas. Berdasarkan tahapan tersebut dapat disimpulkan yaitu 1) 95% guru mampu mengenal aplikasi koding berbasis aplikasi Scratch; 2) 95% guru mampu merancang koding berbasis aplikasi Scratch terintegrasi materi IPA khususnya materi GLB dan GLBB dengan nilai pre-test (52,4%) kategori sedang menjadi meningkat pada nilai pre-test (74,2%) kategori tinggi.